2019
DOI: 10.1080/13563467.2019.1680963
|View full text |Cite
|
Sign up to set email alerts
|

Capitalist Convergence? European (dis?)Integration and the Post-crash Restructuring of French and European Capitalisms

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…This ensures frequent capture by business interests and a pattern of business-government relations characterized by accommodation and co-optation (Jabko & Massoc, 2012). Recent analyses have confirmed that the interpenetration between the public and private sectors allows industries to convince the state to use the European playing field to promote their interests (Ansaloni & Smith, 2018;Clift & McDaniel, 2019). On the contrary, in the British governance ecosystem, the state is more able to autonomously impose its decisions without being excessively concerned by the interests of its business actors (Davis & Walsh, 2016;Weiss, 2020).…”
Section: Relations With Eu Institutions Emphasis On Industrial Benefi...mentioning
confidence: 98%
“…This ensures frequent capture by business interests and a pattern of business-government relations characterized by accommodation and co-optation (Jabko & Massoc, 2012). Recent analyses have confirmed that the interpenetration between the public and private sectors allows industries to convince the state to use the European playing field to promote their interests (Ansaloni & Smith, 2018;Clift & McDaniel, 2019). On the contrary, in the British governance ecosystem, the state is more able to autonomously impose its decisions without being excessively concerned by the interests of its business actors (Davis & Walsh, 2016;Weiss, 2020).…”
Section: Relations With Eu Institutions Emphasis On Industrial Benefi...mentioning
confidence: 98%
“…The gradual transformation of state‐owned network industries into private companies has not prevented the preservation of informal pathways of interaction between government and corporate actors, often oiled by educational and professional homogeneity (Calcara & Marchetti, 2021, pp. 4–5; Clift & McDaniel, 2021). Private governance ecosystems are instead characterized by standard market relationships and enforceable formal contracts (see Table 2).…”
Section: Conceptualizing Government‐industry Interactions In Noisy Po...mentioning
confidence: 99%
“…The ambition to enhance the international standing of the euro is reflected in ongoing attempts to address the incomplete nature of monetary union and to deepen European capital markets (Helleiner, 2015, p. 234). These changes have implications for a growing literature on European disintegration, which has sought to capture the ways in which various pressures potentially combine to unravel the EU project (Clift and McDaniel, 2019; Webber, 2014). Adopting a lens that focuses on the interaction between global financial turbulence and the EU can therefore illuminate how new integrative as well as disintegrative pressures have emerged in the context of the post‐crash world (Lavery et al ., 2019).…”
Section: Theorizing European Integration In An Era Of Global Disordermentioning
confidence: 99%